Effects of destination appeal and tourism infrastructure on rural tourism destination competitiveness and revisit intention: A study in Bario Kelabit Highland - Chee Hua Chin; Winnie Poh Ming Wong; Dayang Zuhaiza Binti Abang Abd Wahap (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2022)
An extensive literature demonstrates that hard dimensions contribute to the growth of tourism destinations. To remain competitive, these resources are significantly important for selecting a tourism location and they also serve as a key attraction for travelers. Therefore, this study is an attempt to explore the effects of hard dimensions (i.e., destination resources, cultural uniqueness, accessibility quality, and accommodation quality) on the competitiveness of rural tourism destination, particularly on highland-based tourism destination. Additionally, this study examines the effect of tourism destination competitiveness on tourists' intention to revisit. Competitiveness theory and theory of planned behavior are used as the theoretical base to explain rural tourism destination competitiveness and tourists' revisit intention. This study surveys 166 respondents comprising of domestic and international tourists. PLS-SEM approach is used to evaluate the developed model, with WarpPLS software performing the PLS estimation and testing of hypotheses. The empirical findings indicate that destination resources, cultural uniqueness, and accessibility quality provided significant contribution to rural tourism destination's competitiveness. Interestingly, it was discovered that the competitiveness of rural tourism destinations has a positive and significant relationship with tourists' intention to revisit. Unexpectedly, a significantly negative relation between accommodation quality and rural tourism destination competitiveness. Ultimately, the study results in development of future guidelines for scholars and practitioners interested in competitive rural tourism destinations.
Keywords: 330; rural tourism destination competitiveness; destination resources; culturaluniqueness; accessibility quality; accommodation quality; revisit intention